HAK DAN KEWAJIBAN ISTRI BAGI WANITA KARIR PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (STUDI KASUS DI PONDOK PESANTREN BAHRUL ‘ULUM AL-ISLAMY KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR RIAU) - Achmad Egi Nurkholis; Ach Faisol; Nur Hasan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The role of career women in the world of work professions. Generally, careers are run by women outside the home. So that career women include those who take part in the public sector. But in the case of career women at the Bahrul 'Ulum Al-islamy Islamic Boarding School, Perhentian Raja District, Kampar Regency, they work only in the cottage environment. A career woman who has an obligation to manage the household as well as possible, always serves her husband and helps her husband to work together to find economic needs so that the mandatory role of a housewife as well as being a career woman can fulfill the requirements that women may work according to legal theory. Islam Buya Yahya.The formulation of the problem in this study are: (1) What are the rights and obligations of the wife who becomes a career woman from the perspective of Islamic law and positive law? (2) What is the perspective of Islamic law and positive law on the dual role of a wife who becomes a career woman? This research is in the form of a sociological approach or empirical legal research. The researcher uses the method in this thesis using a qualitative analysis approach which is intended to examine the final results of in-depth interviews (deep interviews), then analyze the final results of the data obtained in order to conclude the research conclusions. This approach is intended for the views of the ustadzah who at the same time has a structural position within the Bahrul 'Ulum Al-Islamy Islamic Boarding School. Kata kunci: : Rights and Obligations, Career Women, Islamc Law, Positive Law.